Social Acceptance of Vocational Education in China Prompts Students’ Learning Quality: A Moderated Mediation Model - Xia Li; Huilin Deng; Fen Zhang; Mengzhen Ma (SAGE Open)
With the Chinese government’s dedication to equalizing the development of vocational and general education, it is significant to examine how macro-environmental factors in vocational education impact learning processes and outcomes. The paper examines whether social acceptance of vocational education influences learning gains via learning strategies, and investigates the moderating role of social economic status. A survey was completed by 1,323 vocational college students in China, assessing social economic status, social acceptance of vocational education, learning strategies, and learning gains. The results indicated a positive association between social acceptance of vocational education and learning gains. Both deep and surface learning strategies mediated the relationship, with the deep learning strategy accounted for a larger portion of variance. Furthermore, social economic status positively moderated this relationship, reducing reliance on surface learning and enhancing learning gains. The findings underscore the profound influence of social acceptance and social economic status on learning process and outcomes, providing valuable insights for vocational education policy-making and the enhancement of instructional strategies.